glnE Is an Essential Gene in Mycobacterium tuberculosis - Parish, Tanya (American Society for Microbiology, 2000)
Mycobacterium tuberculosis possesses a homologue of glnE, potentially encoding a regulator of glutamine synthetase activity. We attempted to construct glnE-disrupted mutants using a two-step strategy, whereby a single-crossover strain was first isolated, followed by sacB counterselection to isolate the double-crossover strain. Of 192 sucrose-resistant colonies tested, none were mutants, although the wild-type double crossover could be easily isolated. When a second copy of the wild-type glnE was integrated into the chromosome, we could isolate both wild-type and mutant double-crossover strains. Thus, the chromosomal gene could only be replaced with a disrupted copy when another functional copy of the gene was provided, demonstrating that this gene is essential under the conditions tested.